1177 Cost Effectiveness Of Diagnostic Approaches To Sleep Apnea Evaluation During Inpatient Rehabilitation For Moderate To Severe TBI. (27th May 2020) - Nakase-Richardson, R; Dismuke-Greer, C; Jeanne, H; Drashser-Phillips, L; Schwartz, D; Calero, K; Bogner, J; Whyte, J; Almeida, E; Ketchum, J; Magalang, U
Abstract: Introduction: Recent work has highlighted prevalent obstructive sleep apnea (OSA) after traumatic brain injury (TBI) when patients are vulnerable to disruption of neural repair. The recently completed clinical trial comparing screening and diagnostic tools for OSA during inpatient rehabilitation provided the opportunity to conduct economic modeling of phased approaches using actual trial findings to address one perspective (the payor) on the value of phased testing. Methods: A cost-effectiveness analysis of four phased approaches to OSA diagnosis including initial utilization of portable sleep monitoring [HSAT] regardless of pre-test probability, determination of pre-test probability using two prediction models [STOPBANG, MAPI], and initial assessment using Level 1 polysomnography was conducted. The analyses were modeled assuming all participants were considered high risk thus a negative screen or portable diagnostic test would result in a participant being referred for Level 1 polysomnography. The cost aversion used in analyses were derived from a recent white paper on the economic modeling of untreated OSA. Trial data from 214 participants were used in analyses (mean age 44 [SD 18], 82% male, 75% white, with primarily motor-vehicle related injury [44%] and falls [33%] with a sample mean emergency department Glasgow Coma Scale of 8 (SD 5). Results: At AHI ≥15 (33.6%), the prediction models (STOPBANG [-$5, 291], MAPI [-$5, 262]) resulted in greater cost savings and effectiveness relative to the HSAT approach (-$5, 210) and initial use of Level 1 PSG (-$5, 011). Sensitivity analyses at AHI ≥5 (70.1%) revealed the initial use of HSAT (-$6, 322.85) relative to the prediction models (MAPI [-$6, 249.71], STOPBANG [-$6, 237) and initial assessment with Level 1 PSG (-$5, 977) resulted in greater savings and cost effectiveness. Conclusion: The high rates of sleep apnea after TBI highlight the importance of accurate diagnosis and treatment of this comorbid disorder. However, financial and practical barriers exist to obtaining an earlier diagnosis during inpatient rehabilitation hospitalization. Diagnostic cost savings are demonstrated across all phased approaches and OSA severity levels with the most cost-effective approach varying by incidence of OSA. Support: PCORI (CER-1511-33005), GDHS (W91YTZ-13-C-0015; HT0014-19-C-0004)) for DVBIC, NIDILRR (NSDC Grant # 90DPTB00070, #90DP0084, 90DPTB0013-01-00, 90DPTB0008, 90DPT80004-02).